Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.5 Formulas, Applications, and Variation - 7.5 Exercise Set - Page 486: 28



Work Step by Step

Use the rule $\frac{a}{b}=\frac{c}{d} \longrightarrow ad=bc$ to obtain: $$E\cdot R=e(R+r) \\ER=eR+er$$ Subtract $eR$ from both sides: $$ER-eR = er$$ Factor out $R$: $$R(E-e)=er$$ Divide $E-e$ to both sides: $$\frac{R(E-e)}{E-e}=\frac{er}{E-e} \\R=\frac{er}{E-e}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.